Kampo Medicine Promotes Early Recovery From Coronavirus Disease 2019-Related Olfactory Dysfunction: A Retrospective Observational Study - Ono, Rie; Arita, Ryutaro; Takayama, Shin; Kikuchi, Akiko; Ohsawa, Minoru; Saito, Natsumi; Suzuki, Satoko; Ishii, Tadashi (Frontiers in Pharmacology, 2022)
Background: Olfactory dysfunction is a common symptom in patients with coronavirus disease 2019, and it significantly reduces patients’ quality of life. Effective treatments remain unknown. Purpose: To assess the effect of Japanese traditional (Kampo) medicine on coronavirus disease 2019-related olfactory dysfunction. Study Design: Retrospective observational study. Methods: In total, 87 patients aged ≥18 years with coronavirus disease 2019 and severe dysosmia or anosmia (numeric rating scale, ≥7) in isolation facilities in Miyagi Prefecture, Japan, were enrolled from October 2020 to March 2021. Patients were divided into the Kampo group (N=52) and the control group (N=35) based on the treatment received. Changes in numeric rating scale scores were evaluated at the first visit and 2 weeks after the first visit. Results: The median reduction in the olfactory dysfunction score at both 1 and 2 weeks after the first visit was significantly greater in the Kampo group (6 and 8, respectively) than in the control group (3 and 7, respectively) (P=0.03 and P=0.04, respectively). We defined improvement in olfactory dysfunction as a median reduction in the olfactory dysfunction score of ≥5. Multiple logistic regression analysis demonstrated that only Kampo treatment was significantly associated with an improvement in olfactory dysfunction. Conclusion: This study suggested that Kampo medication promotes early recovery from coronavirus disease 2019-related olfactory dysfunction.